2011
DOI: 10.1111/j.1743-6109.2011.02439.x
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Sexual Self-Disclosure to Sexual Satisfaction and Functioning in Committed Relationships

Abstract: Introduction Past research indicates that sexual self-disclosure, or the degree to which an individual is open with his or her partner about sexual preferences, is a key aspect of sexual satisfaction and that partner's lack of knowledge about one's sexual preferences is associated with persistent sexual dysfunction. Aims To replicate and extend past research by examining (i) how one's own levels of sexual self-disclosure are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 15 publications
7
53
0
8
Order By: Relevance
“…There is a burgeoning body of research showing that more disclosure to one's partner about sexual preferences and desires (which is conceptualized in this study as “sexual communication content”) is positively correlated with sexual satisfaction and relationship quality (e.g., Byers & Demmons, ; MacNeil & Byers, ; Mark & Jozkowski, ; Montesi, Fauber, Gordon, & Heimberg, ; Rehman et al., ). Conversely, those that are less satisfied sexually and relationally are often more avoidant or indirect in their approach to communication (Montesi et al., ; Theiss, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a burgeoning body of research showing that more disclosure to one's partner about sexual preferences and desires (which is conceptualized in this study as “sexual communication content”) is positively correlated with sexual satisfaction and relationship quality (e.g., Byers & Demmons, ; MacNeil & Byers, ; Mark & Jozkowski, ; Montesi, Fauber, Gordon, & Heimberg, ; Rehman et al., ). Conversely, those that are less satisfied sexually and relationally are often more avoidant or indirect in their approach to communication (Montesi et al., ; Theiss, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Observed empathic response was examined in the listener only. The development of the observed disclosure measure was complex considering that far less attention has been given to the development of an observational measure of disclosure in comparison to an observational measure of empathic response and to self-reported measures of disclosure (Cano et al, 2010;Rehman, et al, 2011).…”
Section: Observed Disclosure Is Not Associated With Sexual Satisfactimentioning
confidence: 99%
“…Researchers have demonstrated that sexual self-disclosure between intimate partners, in committed or long-term relationships, is associated with sexual satisfaction (Byers & Demmons, 2010;MacNeil & Byers, 1997, 2009Rehman et al, 2011). Cupach and Metts (1991) suggested that disclosing one's sexual likes and dislikes can serve as a tool for informing one's partner of one's preferences, and thereby enable one to obtain more of what one wants (and less of what one does not want) from one's partner, thus increasing sexual satisfaction.…”
Section: Sexual Self-disclosure and Sexual Satisfactionmentioning
confidence: 99%